Proximate, Mineral and Phenol Content of Dioscorea Rotundata Var. Amula, Dioscorea Cayenensis Var. Igangan-Alo from Farmers’ Plots and Bounty-Fertilized, Infected with Botryodiplodia Theobromae Pat. - Otusanya, M. O. (European Journal of Applied Sciences, 2021)
Fertilizer effects on infection and weight loss by Botryodiplodia theobromae Pat, was determined in white guinea yam Dioscorea rotundata variety Amula from the middle belt-region of Nigeria, and yellow guinea yam D. cayenensis variety Igangan/Alo from South West Nigeria. Tubers of both varieties were sourced from farmers’ plots from within Ogun State ( South West Nigeria) where they had been planted on three or more years previously fallowed plots, and harvested at six months after planting. Another lot of tubers of both varieties were sourced from a yam project plot at the Teaching and Research farms of the Directorate of University Farms (DUFARMS), Federal University of Agriculture (FUNAAB) Abeokuta, where they had been fertilized at the rate of 0.60 ml l-1 of Bounty fertilizer, an 8-mineral component fertilizer, and harvested also at six months after planting. Tubers of both varieties from farmers’ plots were analysed for proximate content (dry matter, moisture, ash, fat, crude protein, crude fibre and carbohydrate) phenol content and ten minerals namely Ca, N, P, K, Mg, Fe, Mn, S, Zn and B. Another set of tubers of the two varieties from farmers plots, as well as those from the Bounty-fertilized yam project plot, were inoculated with Botryodiplodia theobromae in an infection and weight loss experiment. The infection and weight loss experiment was a 2 by 2 factorial arranged in RCBD (randomized complete block design) with 4 treatment combinations and 5 replications. Tubers of both varieties from both sources inoculated with a 7-day old pure culture of B. theobromae were the four treatment combinations. Incubation period was 3 weeks. Infection in Amula (white guinea yam) was over 2500% higher than in the yellow guinea yam, Igangan. Phenol (107.89 mg/100 gdm) and calcium (16.85 mg/100 gdm) were higher in Igangan than in Amula (89.04 and 16.70 mg/100gdm respectively), and is adduced as the reason for the high infection in variety Amula. Weight loss however was 154% higher in Igangan than in Amula. Crude fibre had a negative significant correlation with weight loss (r = -0.9285, P=0.001), and crude fibre with the value 4.49% dm was higher in variety Amula than in variety Igangan (4.02%dm). This is responsible for the higher weight loss in var. Igangan. Phenol content also had a significant negative correlation with weight loss (r = -0.9586, P = 0.05), suggesting that the effect of high crude fibre in reducing weight loss outweighs that of phenol in reducing weight loss. There was high reduction of infection in the Bounty-fertilized tubers, 3.72% compared to farmers’ plot tubers which had 27.22%. Weight loss was also 0% in Bounty-fertilized tubers compared to a high 63.54% in the tubers from farmers’ plots. This indicates that the 8-mineral component fertilizer, Bounty will prolong shelf life in the white and yellow guinea yams Amula and Igangan. Five minerals namely Mg, K, Zn, Mn and B had significant correlation with weight loss (r = 0.9461, 0.9802, 0.9214, 0.9898 and 0.9122) respectively. Three of these minerals namely Zn, Mn and B content were all low with mean values of 0.25, 0.44 and 0.07 mg/100gdm respectively but Mg and K were relatively higher with mean values of 21.59 and 806.67mg/100gdm respectively. This suggests that mineral nutrition to enhance prolonged shelf life in D. rotundata var. Amula and D. cayanensis var. Igangan may be established with a balance of Mg, Zn, Mn and B in lower proportions than K, as potassium is essential in optimum yield in Dioscorea species.